LANGKAH INDONESIA DALAM MENGHADAPI HAMBATAN EKSPOR OTOMOTIF KE VIETNAM TAHUN 2018 - Eri Yanto; Ahmad Fuadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research is written in account to Prime Minister Degree No. 116/2017/ND-CP and Circular No. 04/2018/TT-BGTVT. Which halts all vehicular exports from Indonesia to Vietnam since January 1st 2018. Indonesian is known as a country that has exported 27,840-36,469 cars in 2017 and 2018.The perspective that is used in this research is the liberalism perspective. The perspective in which all business actors, whether domestic or foreign plays an important role in the global economy process. The theory that is used is the diplomacy theory with negotiation concept and nation state level of analysis.Indonesian conducted a negotiation mechanism in resolving automotive export barriers to Vietnam. Indonesian government complied to the Vietnamese government request to fulfill Vehicle Type Approval (VTA) certificate CBU in order to adjust to the import regulations applied in Vietnam. Keywords : Indonesian Government, Vietnamese Government, VTA, Gaikindo, Diolomacy, VAMA, Negotiation.